A Relational Theory of Earnings Inequality. (March 2014) - Avent-Holt, Dustin; Tomaskovic-Devey, Donald
Most research on earnings adopts economist's human capital model. In doing so, social scientists, explicitly or implicitly, cede primacy to the labor supply and demand mechanisms of neoclassical economics. In contrast we develop a model that treats actors' claims as the central mechanism generating inequalities. In this model earnings are most proximately a result of negotiation between actors embedded in a set of social relations within organizations, a process we refer to as relational claims-making . Institutional and competitive aspects of organizational environments, as well as social distinctions within organizations themselves, provide resources and constraints on the persuasiveness and plausibility of wage claims by actors. Market mechanisms are not causally proximate to the production of wage inequality, but rather are an aspect of actor's environments with the potential to influence the plausibility of particular claims.